Infestação e controle de insetos pragas no cafeeiro em Areia-PB - Souza Junior, Silvio Lisboa de (2024)
The coffee tree stands out as one of the main commodities in global agribusiness, being of great relevance not only economically, but also being directly linked to the culture in several countries, as is the case in Brazil, this is due to the high added value of the culture and the its productive adaptability. Despite the aforementioned relevance, the production chain still suffers greatly due to the lack of adequate management and the large presence of insect pests that affect it during its cycle, such as the miner bug, the coffee borer and the coffee cochineal, thus causing several losses in its production. Therefore, it is necessary to evaluate the damage caused by insect pests and search for effective methods to reduce productivity loss. Therefore, this study aimed to evaluate the incidence of pests that affect coffee farming in the state of Paraíba, as well as evaluate chemical and biological control methods to reduce productivity losses caused by insect pests. The experimental design used was randomized blocks, with three blocks and 10 replications per treatment. To evaluate C. parahybenses and H. hampei, 6 varieties of C. arábica were used: Catuaí red 144, Catuaí yellow 62, Catucaí 24137, Mundo novo, Arara and Bourbon in their 3rd production cycle, observing the presence of attack of these insects on the varieties. To control L. coffeella, an area of C. arabica was used in its 4th production cycle, evaluating the number of galleries formed by the insect by testing 7 treatments: Metarhizium, Potassium Silicate, Metarhizium + Potassium Silicate, Metarhizium + Beauveria , Bold™, Match™ and Control (Water). The data were subjected to statistical analysis using the binomial model with overdispersion to evaluate the incidence of H. hampei and C. parahybenses. For L. coffeella, data were subjected to the F test using the generalized linear model, and physiological data were analyzed using hierarchical clustering. There was no statistically significant difference between the tested varieties in relation to the incidence of H. hampei and C. parahybenses. The Bold™ insecticide presented the best metrics for controlling L. coffeella in comparison to the other products evaluated, in addition to demonstrating the best physiological responses.